Essays on economic mobility - Yalonetzky, GI (2008)
This thesis is a collection of three essays with contributions to the intergenerational and intra-generational mobility literature. The essay on full risk insurance and measurement error examines the likelihood that measurement error may reconcile observed departures from perfect rank immobility in insurable consumption with the mobility predictions of full risk insurance, by generating spurious rank-breaking transitions. The essay shows that under certain assumptions full risk insurance predicts perfect rank immobility and that there exists ranges of error covariance matrices for which the mobility predictions of full risk insurance plus measurement error can not be rejected in the Peruvian data. A novel approach to test these mobility predictions is presented. The essay on discrete time-states Markov chain models applied to welfare dynamics shows that models with higher order may fit data better than the popular first-order, stationary model, and that the order of the chain, in turn, affects the estimation of equilibrium distributions. A best-practice methodology to conduct homogeneity tests between two samples with different optimal order is proposed, and an index by Shorrocks, based on the trace of the transition matrix, is extended to discrete Markov chain models with higher order. The essay on cohort heterogeneity in intergenerational mobility of education shows how cohort heterogeneity affects the analysis of cross-group homogeneity and long-term prospects of a welfare variable, based on transition matrix analysis. The essay compares the transition matrices of Peruvian groups divided by gender and ethnicity and finds genuine reductions in heterogeneity of the mobility regimes between male and female and between indigenous and non-indigenous groups among the youngest cohorts. The essay proposes a methodology to conduct first-order stochastic dominance analysis with equilibrium distributions and shows that among the youngest cohorts past stochastic dominance of male over females and non-indigenous over indigenous disappear in the long term.